ANALYSIS OF WMA METHOD FOR FORECASTING COOKING OIL STOCK AT AWI MARKET - Windy Antika Putri; Rizky Fauziah; Adi Mas Afandi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Cooking oil is a cooking ingredient made from palm oil. Cooking oil is one of the basic necessities used for the cooking process. Awi Market's cooking oil sales have experienced fluctuations or ups and downs in cooking oil sales. This is due to the instability of cooking oil sales, making Awi Market owners have difficulty determining the amount of cooking oil stock that will be sold in the next period. The purpose of this study is to predict the stock of cooking oil using the WMA method so that the stock of cooking oil in the following month can be fulfilled. the results of applying the Weighted Moving Average method to predict cooking oil stocks at Awi Market in May 2022, there will be 86.67 bimoli cooking oil stocks available with 19.97% MAPE error accuracy, 93.33 fortune with 20% MAPE error accuracy, sunco as much as 78.33 with 31.87% MAPE error accuracy, 53.33 tropicana slim with 29.74% MAPE error accuracy and rose brand as much as 55 per pack with 26.27% MAPE error accuracy. So it can be concluded that the WMA method can help the supply of cooking oil in the following month quickly and accurately.